Feminist Activism, Travel and Translation Around 1900 Transnational Practices of Mediation and the Case of Käthe Schirmacher - Gehmacher, Johanna (Translation History, 2024)
This open access book takes the biographical case of German feminist Käthe Schirmacher (1865-1930), a multilingual translator, widely travelled writer of fiction and non-fiction, and a disputatious activist to examine the travel and translation of ideas between the women's movements that emerged in many countries in the late 19th and early 20th century. It discusses practices such as translating, interpreting, and excerpting from journals and books that spawned and supported transnational civic spaces and develops a theoretical framework to analyse these practices. It examines translations of literary, scholarly and political texts and their contexts. The book will be of interest to academics as well as undergraduate and postgraduate students in the fields of modern history, women's and gender history, cultural studies, transnational and transfer history, translation studies, history and theory of biography.